Researching a Community in Transition - Ieva Weaver (Music & Minorities)
Since 2004, when Latvia joined the European Union, nearly half of the Latvian Roma have moved abroad, mainly to the UK. This fact has influenced the research on Latvian Roma music. The article self-reflexively explores migration as “losing” a fieldwork community and coping with the loss. A digital action for re-connecting with the Roma community was establishing a Facebook group, “Latvijas romu vēsture un kultūra” (“History and Culture of Latvian Roma”), in the summer of 2019. Initially, the group was defined as a one-way commitment to share historical sources with Roma and people interested in Roma history and culture. Gradually, the group shifted from being primarily a science communication tool to digital participative ethnography. A part of it was exploring Roma’s engagement with music-related content. Another chapter is based on recent fieldwork with Latvian Roma in England. The fieldwork took place among born-again Christian Roma and their established churches and reflected on the traditional Romani values and behavior in this context. The author identifies a triple mobility – physical, social and spiritual – which necessitates a redefinition of the existing framework for researching the Latvian Roma. The article concludes with a reflection on a field-centric, community-centric approach as an interdisciplinary-oriented research practice.